Dynamic characteristics of exponential slider bearings lubricated with a ferrofluid – Shliomis model. Issue 4 (8th May 2018) - Lin, Jaw-Ren; Chu, Li-Ming
Abstract : Purpose: The purpose of this paper is to investigate the dynamic characteristics of exponential slider bearings lubricated with a ferrofluid. Because of the development of modern engineering, the increasing use of ferrofluids in lubrication fields has shown great importance. Understanding the dynamic characteristics of exponential film bearings is helpful for engineers in bearing selection. Design/methodology/approach: Applying the Shliomis ferrohydrodynamic flow model and considering the squeezing action of bearing pads, a dynamic Reynolds equation is obtained for an exponential film slider bearing lubricated with a ferrofluid in the presence of a transverse magnetic field. Analytical solutions of dynamic characteristics are obtained. Findings: According to the results, the ferrofluid-lubricated exponential film bearing provides better dynamic stiffness and damping characteristics than the non-ferrofluid ones, especially the bearing operating at higher values of the volume concentration parameter and the magnetic Langevin parameter. Originality/value: Numerical tables of stiffness and damping coefficients for different values of the volume concentration parameter and the Langevin parameter are also included for engineering references.